PENGARUH ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB), LINGKUNGAN KERJA, DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA PT BANK BRI CABANG RAJAWALI SURABAYA - Rahayu, Ida Susana Tri; Herachwati, Nuri (JURNAL LENTERA BISNIS, 2025)
Employee performance is a key element in maintaining competitive advantage in human resources, especially in competitive banking sectors such as PT Bank BRI Rajawali Surabaya Branch. This study aims to analyze the influence of Organizational Citizenship Behavior (OCB), work environment, and organizational culture on employee performance. The method used is a quantitative approach through a survey of 100 employees from various divisions. Data analysis was conducted using multiple linear regression with the assistance of SPSS 25. The research results indicate that OCB, work environment, and organizational culture significantly influence employee performance. These findings indicate that improvements in employee performance are more determined by voluntary work behavior and supportive work conditions, as well as internalized organizational cultural norms. This study recommends strengthening OCB, improving the work environment, and organizational culture as strategies for enhancing performance at the branch level.